“The Aesthetics of Reception between Interpretation and Hermeneutics.” - bensadek, khawla.; delloum, mohamed. (El Omda in Linguistics and Discourse Analysis, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:71a7b197-9dea-4735-85eb-26e3a97f4765-11" data-testid="conversation-turn-24" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="577681f9-607f-4d7e-99a0-9ad45ce8eed6" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> Reception is considered one of the central concepts in contemporary critical studies, as modern theory has moved beyond the traditional binary (text/author) to place the reader at the heart of the creative process. Through this shift, a new approach has emerged that highlights interpretation as a preliminary stage for understanding the surface meaning of the text, and hermeneutics as an openness to the potential worlds of meaning. The aesthetics of reception is manifested in the balance between these two dimensions, where a text cannot attain its lasting significance except through the dialectic of interpretation and hermeneutics. This study seeks to investigate the roots of reception theory in both Arabic and Western criticism, highlighting the contributions of Hans Robert Jauss and Wolfgang Iser, among others, as well as tracing the reflection of these concepts in modern Arabic criticism.